Digital contracts: Thinking in trends - Кіріяк; Kiriiak, Оксана; Oksana (My University, 2020)
In the context of globalization and integration of private law practices, the issue of proper execution and valid certification of digital contracts is becoming increasingly important. In this article, we try to make a thorough analysis of the main trend determinants that determine the development of digital contracts, both in everyday life and in emergencies caused by the spread of acute respiratory disease caused by the virus COVID-19. This article demonstrates the conclusions we reached as a result of the study and allows us to formulate general vectors for the subsequent digitalization of legal relations.
Keywords: contract; digital contracts; digitalization; digital agreements; e-contracts.; contract; digital contracts; digitalization; digital agreements; e-contracts